Hur gör djur? Människor, andra djur och utmaningar för sociologin (Sociologisk Forskning, 2006)
This article addresses the issue that even though we can witness a change in attitudes and practices towards animals in contemporary western society, main stream sociology has been reluctant to treat research on human-animal relations seriously. The point made is that such research should be of great interest, not just for empirical reasons, but also because human-animal interaction challenges some of our most common sociological concepts and traditions. With the help of some illustrative examples from the zoological park o f Slottsskogen, Göteborg, I review some new currents from the field of the sociology of human-animal relations and investigate such challenges with regards to concepts like interaction, personification and social identity. Some less common concepts, derived from the same research field, such as anima urbis, speciesism and significant otherness, also get introduced. The article concludes that mainstream sociology could learn a lot from this sub-field, and I especially draw on symbolic interactionism, urban research and feminism to make that claim.
Keywords: human-animal relations; interaction; urban animal; symbolic interactionism